2016
DOI: 10.1021/acsami.6b08320
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Catalytic Activity of a Metal–Organic Framework Derived Copper and Nitrogen Co-Doped Carbon Composite for Oxygen Reduction Reaction

Abstract: An efficient non-noble metal catalyst for the oxygen reduction reaction (ORR) is of great importance for the fabrication of cost-effective fuel cells. Nitrogen-doped carbons with various transition metal co-dopants have emerged as attractive candidates to replace the expensive platinum catalysts. Here we report the preparation of various copper- and nitrogen-doped carbon materials as highly efficient ORR catalysts by pyrolyzing porphyrin based metal organic frameworks and investigate the effects of air impurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…The satellite peak of Co 2p 3/2 at 785.2 eV waso bserved, which was similar to those of Co@NC ( Figure S6 in the Supporting Information). [74,85,86] The Nc ontentsi nC uCo@NC, Co@NC, and NC are calculated to be 3.83, 3.71, and 1.04 at %, respectively,w hich are much higher than that in Co encapsulated with N-doped carbon derived from ZIF-L. [73] NC was derived from ZIF-L-Zn at 900 8Ci n Ar,w hich has the same topological structure as ZIF-L-Co and is used as ar eference. The Cu 2p satellite peak at 944.2 eV can be attributed to Cu II species in CuCo@NC owing to the unfilled electron state of Cu 3d 9 orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…The satellite peak of Co 2p 3/2 at 785.2 eV waso bserved, which was similar to those of Co@NC ( Figure S6 in the Supporting Information). [74,85,86] The Nc ontentsi nC uCo@NC, Co@NC, and NC are calculated to be 3.83, 3.71, and 1.04 at %, respectively,w hich are much higher than that in Co encapsulated with N-doped carbon derived from ZIF-L. [73] NC was derived from ZIF-L-Zn at 900 8Ci n Ar,w hich has the same topological structure as ZIF-L-Co and is used as ar eference. The Cu 2p satellite peak at 944.2 eV can be attributed to Cu II species in CuCo@NC owing to the unfilled electron state of Cu 3d 9 orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…Tremendous investigations regarding Cu‐based ORR catalysts were preformed, including CuO/carbons, Cu−N‐doped carbons, copper complexes and Cu/carbons ,. For example, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous investigations regarding Cu-based ORR catalysts were preformed, including CuO/carbons, [20] CuÀN-doped carbons, [21][22][23][24][25][26][27] copper complexes [28][29][30][31][32][33] and Cu/carbons. [34,35] For example, Wang et al reported a copper complexes sandwiched between polyvinylimidazole layers wrapped on carbon nanotubes catalyst [30] and TiO 2 -grafted copper complexes deposited on multiwalled carbon nanotubes (CNTs), [31] which exhibit a ORR activity comparable to Pt/C catalyst in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Thus, a challenge exists to develop cost-effective and active nonprecious-metal nanostructures to replace PGM-ORR catalysts in large-scale energy technologies, particularly in fuel cells and metal-air batteries. [12][13][14][15] Nevertheless, it remains challenging to prepare composites featuring more metal active sites and thinner graphitic carbon coatings to facilitate excellent electrolyte utilization and mass transport during the ORR. [6][7][8] Recently, composites of transition metals and carbon have attracted attention because of their stable (metal) active sites and low degrees of (carbon) corrosion in harsh electrolyte environments.…”
Section: Introductionmentioning
confidence: 99%